Reciprocal cross-protection induced by sporozoite antigens SPAG-1 from Theileria annulata and p67 from Theileria parva - Hall, R.; Boulter, N.R.; Brown, C.G.D.; Wilkie, G.; Kirvar, E.; Nene, Vishvanath M.; Musoke, A.J.; Glass, E.J.; Morzaria, S.P. (Wiley, 2000)
Theileria annulata and Theileria parva both poses a major surface antigen on the sporozoite stage of the life-cycle, called SPAG-1 and p67, respectively. In each case, these antigens are vaccine candidates and have been shown to induce a degree of homologous protection in earlier work. These antigens share sequence homology and are serologically cross-reactive. Here, we confirm that these antigens confer protection against homologous species challenge. More importantly, they mutually confer a degree of cross-species protection raising the prospect of a common vaccine in the future.